Why we buy? Culture as a buying motivator - Askegaard, Søren (Henry Stewart Talks, 2013)
Individual and culture, Semiotics, Movement of meaning in the world of goods, Cultural categories and principles, Why we buy (culture) -Marketing and culture, Consumer culture theory, Globalization & Glocalization, Cultural reflexivity, Yoga as HRM, health practice and market power, Globalizing Western myth of authenticity
Reviewed at 2019/09/26